An examination of state and local government pension underfunding – Implications and guidance for governance and regulation. Issue 2 (October 2018) - Foltin, Craig
Abstract: State and local government pension underfunding has become a major focus of public policy debate due in large part to recent Governmental Accounting Standards Board (GASB) actions that have brought national attention to the issue. The extent of these plans underfunding has been debated, along with the necessity for state government intervention and the level of regulatory actions that should be enacted by state legislatures. State and local public pension plans do not fall under the enumerated powers of the federal government in the Constitution and are therefore left to each individual state to regulate. The amount of plan underfunding and enacted public policy by state varies greatly. Additionally, in contrast to numerous state balanced-budget laws, legal directives for fully funding public pensions are virtually non-existent. This paper analyzes the state and local public pension crisis, examines current and long-term risk, studies public employee fiscal conditions, considers the societal impacts of these plans, considers the strengths and weakness of pension plan types, recommends public policy and regulation, and offers strategies for managers, board members, and public officials to adopt.